(untitled) (Communications in Computational Physics, 2006)
In this work, the modified Ghost Fluid Method is further developed to apply to compressible fluid coupled to deformable structure, where the pressure in the structure or flow can vary from an initial extremely high magnitude (such that the solid medium can be under plastic compression) to a subsequently very low quantity (so that cavitation can occur in the fluid). New techniques are also developed in the definition of the ghost fluid status when the structure is under plastic deformation or when the flow is under cavitation next to the structure. Numerical results show that the improved MGFM for treatment of the fluid-deformable structure coupling works efficiently for all pressure ranges and is capable of simulating cavitation evolution and cavitation reloading in conjunction with the employment of the isentropic one-fluid cavitation model.